1995
DOI: 10.1037/1064-1297.3.3.252
|View full text |Cite
|
Sign up to set email alerts
|

Effects of negative modulators of GABAergic efficacy on ethanol intake: Correlation of biochemical changes with pharmacological effect using a behavioral paradigm.

Abstract: Negative allosteric modulators of varying intrinsic efficacies that reduce GABAergic function were evaluated for the ability to decrease the reinforcing properties of ethanol (EtOH) in the selectively bred alcohol-preferring (P) rats. Pretreatment with negative modulators maximally reduced EtOH intake during the initial 15-min interval to 9% to 49% of control levels; however, rank-order potencies of negative modulators to attenuate EtOH intake were not correlated with rank-order potencies of negative modulator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 31 publications
(67 reference statements)
0
3
0
Order By: Relevance
“…Previously, we reported that rank order potencies of BDZs to attenuate EtOH intake were not correlated with rank order potencies of BDZs to inhibit GABA 36 Cl Ϫ conductance and enhance 35 S-t-butylbicyclophosphorothionate (TBPS) binding (June et al, 1995). Whereas the 36 Cl Ϫ flux and TBPS binding assays use heterogenous subunit populations, with the resulting value obtained representing an "average efficacy," the Xenopus oocyte system permits efficacy to be determined at any different subunit-cDNA combinations (Pritchett et al, 1989;Wafford et al, 1993).…”
Section: Subunit Selectivity Versus Intrinsic Activitymentioning
confidence: 98%
“…Previously, we reported that rank order potencies of BDZs to attenuate EtOH intake were not correlated with rank order potencies of BDZs to inhibit GABA 36 Cl Ϫ conductance and enhance 35 S-t-butylbicyclophosphorothionate (TBPS) binding (June et al, 1995). Whereas the 36 Cl Ϫ flux and TBPS binding assays use heterogenous subunit populations, with the resulting value obtained representing an "average efficacy," the Xenopus oocyte system permits efficacy to be determined at any different subunit-cDNA combinations (Pritchett et al, 1989;Wafford et al, 1993).…”
Section: Subunit Selectivity Versus Intrinsic Activitymentioning
confidence: 98%
“…To habituate the rats to the activity monitor prior to any drug treatment, rats were given five daily 10-min sessions (June et al 1995a(June et al , 1995b(June et al , 1998b. These sessions thoroughly habituated the animals to the open field arena.…”
Section: Training and Acclimation Phasementioning
confidence: 99%
“…Alcohol's ability to potentiate the activity of γ‐aminobutyric acid (GABA) at GABA A receptors has been implicated as a key mechanism underlying the abuse‐related effects of alcohol in both human and nonhuman subjects (e.g., Hyytiä and Koob, ; June et al., , ; Korpi, ; Söderpalm and Hansen, ). Molecular biological studies have shown that the mammalian GABA A receptor is a pentamer consisting of subunits from at least 5 different families, including the α, β, and γ subunits (McKernan and Whiting, ; Pritchett et al., ; Rudolph et al., ).…”
mentioning
confidence: 99%